2014
DOI: 10.1002/elps.201300581
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cell type‐specific proteome signatures of primary human leukocytes, endothelial cells, keratinocytes, hepatocytes, fibroblasts and melanocytes by comparative proteome profiling

Abstract: Cells gain their functional specialization by different protein synthesis. A lot of knowledge with respect to cell type-specific proteins has been collected during the last thirty years. This knowledge was built mainly by using antibodies. Nowadays, modern MS, which supports comprehensive proteome analyses of biological samples, may render possible the search for cell type-specific proteins as well. However, a therefore necessary systematic MS study comprising many different cell types has not been performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…In addition, we identified Ras‐interacting protein 1 (RAIN) as being overexpressed in ECs. We can consider RAIN ‐ known to be essential for endothelial cell morphogenesis and blood vessel tubulogenes ‐ as being a part of the specific signature for ECs , in consistency with other recent proteomic study .…”
Section: Discussionsupporting
confidence: 87%
“…In addition, we identified Ras‐interacting protein 1 (RAIN) as being overexpressed in ECs. We can consider RAIN ‐ known to be essential for endothelial cell morphogenesis and blood vessel tubulogenes ‐ as being a part of the specific signature for ECs , in consistency with other recent proteomic study .…”
Section: Discussionsupporting
confidence: 87%
“…In order to understand the underlying mechanisms of transformation of keratinocytes to SCC, we simulated a stepwise development from (i) normal keratinocytes through (ii) inflamed keratinocytes to (iii) skin cancer. As in our earlier study [19], we showed that, using comparative proteome profiling with high-throughput proteomics and bioinformatics, we can identify proteins that are highly specific for a particular cell type, as well as potential new candidate proteins.…”
Section: Discussionsupporting
confidence: 65%
“…These cells have been analyzed by us previously (11,12) demonstrating that they display all relevant cell type characteristics of stromal fibroblasts and endothelial cells, and thus represent suitable model systems. A standardized approach has been applied to semi-quantitatively determine and compare the relevant regulatory factors that were up-and downregulated by fibroblasts and endothelial cells upon inflammatory activation.…”
mentioning
confidence: 99%